TINGKAT FAKTOR RISIKO STROKE DENGAN PENGETAHUAN MASYARAKAT TERHADAP DETEKSI DINI PENYAKIT STROKE - Musafaah; Faisal, Haris; Rachmawati, Kurnia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Stroke is an acute neurology deficit disease which is caused by many risk faktors(multicausal)andinteraction of that risk faktors can increase risk to get stroke in the future. Comprehensive preventionand identification of stroke disease will be useful to reduce the impact of stroke attack. This researchaimed to know the relationship between the level of stroke risk faktors and people knowledge aboutearly detection of stroke disease. This research was analytical with Cross Sectional approach. Therespondents of this research was 40 peoples. Analysis data used correlation statistical from SpearmanRank. The outcome showed that there was no relationship between the level of stroke risk faktors andcommunity’s knowledge about early detection of stroke disease in Public Health Center of Cempaka(p = 0,66; α = 0,05).